Education PENDAMPINGAN BAGI FOS PSK (PEDULI SESAMA KITA) MELALUI PROGRAM LITTLE STAR CERDAS BERBAHASA INGGRIS DI DESA KETING, JEMBER: ASSISTANCE FOR FOS PSK (CARE FOR OUR NEIGHBORS) THROUGH THE ENGLISH LANGUAGE SMART LITTLE STAR PROGRAM IN KETING VILLAGE, JEMBER - Cendy Nur Faizah Putri; Gresafril Wisnu Dwi; Aulia Chayyuna; Rishad Kurniawan Kuncoro; Moh. Nazib Abdulloh Yaqin (Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
Education is a learning process including teaching a skill, providing knowledge, consideration and wisdom. The education path consists of two types, namely formal education, namely through school and non-formal education, namely outside school. Education outside of school or non-formal is carried out to support or increase students' knowledge about learning material at school. Keting Village, Jember Regency has an independent social organization under the name FOS PSK (Cares for Our Neighbors). The organization has a program called Little Star that teaches kindergarten and elementary school children in English subjects to improve their knowledge and understanding. This study describes Collaborative KKN students in visits and mentoring activities at FOS PSK (Cares for Our Neighbors)in the Little Star program. The methods used are interview and execution methods. Interviews were conducted between students and administrators and teachers of PSK to find out the condition of understanding English and the problems faced by the Little Star program. The implementation of mentoring is carried out by students accompanied by PSK lecturers twice on Sundays. The mentoring activities carried out consisted of several activities, namely gymnastics, giving material, and practice questions combined with prize games. Little Star children show a high interest in learning English because of the learning combined with prize play.